Patronage politics as a driver of economic regionalisation: the Indonesian oil palm sector and transboundary haze - Varkkey, Helena (Wiley, 2012)
Recent evidence has linked illegal peat and forest fires in Indonesia to commercial oil palm plantations. Fire is the most cost-efficient way to clear land for planting, but these fires release smoke causing transboundary haze pollution. The countries worst affected by the haze are neighbouring Malaysia and Singapore. Malaysian and Singaporean investors control more than two-thirds of the Indonesian oil palm plantation sector and they have been implicated in the fires alongside local plantations. Using information obtained from interviews with individuals linked to the sector, this paper aims to explain why these companies continue to burn despite the dire consequences of the haze. It identifies patronage politics as a common business culture in Southeast Asia, and argues that because these Malaysian and Singaporean investors are already familiar with patronage practices at home, they have easily inserted themselves into existing patronage networks in Indonesia. Hence, these companies enjoy the protection of their Indonesian patrons during their operations. Furthermore, in a business atmosphere defined by patronage politics, clients are largely motivated by material gain. This explains why Malaysian and Singaporean investors continue to clear land by fire in the interests of cost-efficiency, despite their home countries suffering the worst effects of haze.